Analisis Sitasi Dalam Kajian Bibliometrika Pada Jurnal Communications In Science and Technology Periode 2021-2023 - Nalole, Suci Ramadhani; Azizah, Ika Nur (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2025)
Background of the Study: Citation analysis is a key component of bibliometric studies used to examine patterns in literature usage and knowledge dissemination. Despite the growing prominence of the Communications in Science and Technology (CST) journal in the field of exact sciences, no prior research has analyzed its citation patterns. Understanding these patterns is essential for assessing the journal’s scholarly impact and guiding its future development. Objectives: This study aims to identify the pattern of literature usage in articles published in the Communications in Science and Technology (CST) journal and to provide an overview of the journal’s overall condition. The analysis results can serve as a source of information to understand the knowledge flow within the journal and support its future development. Method: The method used is a bibliometric study to analyse citations in the Communications in Science and Technology (CST) journal. Data collection was carried out by downloading citations found in the Communications in Science and Technology (CST) journal from 2021-2023. Data analysis uses descriptive statistics. Finding: The result of this research showed that in the period 2021–2023, the Communications in Science and Technology (CST) journal had a citation half-life value of 9,5 years. On average, the journal’s citation half-life is 10 years. Conclusion: The Communications in Science and Technology (CST) journal during 2021–2023 the citations cited from 1963 to 1972 with a total of 4 citations are considered obsolete. Meanwhile, citations from 1973 to 2023 with a total of 2466 citations are considered valid. The number of references used as citations in the CST journal is 2470 citations. The most widely used type of language is English with 2463 titles. The types of literature that are often used are 1917 articles.